Impact of smoking cessation on non-alcoholic fatty liver disease prevalence: a systematic review and meta-analysis - Qinghua Yang; Guang Ji; Shengan Zhang; Zhidong Liu; Zichun Hu; Wenjun Zhou; Yanqi Dang (BMJ Open)
Objectives The negative effects of smoking on numerous cardiovascular and metabolic diseases have been widely acknowledged. However, the potential effect of smoking cessation is relatively unelucidated. The objective of this study is to explore whether the prevalence of non-alcoholic fatty liver disease (NAFLD) in former smokers differs from the prevalence in current smokers.Design Systematic review and meta-analysis.Data sources Four databases, that is, PubMed, Web of Science, Journal@Ovid and Scopus were searched from inception to 31 January 2023.Eligibility criteria Population-based cross-sectional studies, including the baseline data of cohort studies with identified NAFLD diagnostic methods, and smoking status (current smoker or former smoker) of participants were included.Data extraction and synthesis Two reviewers independently extracted the data including cigarette smoking status, country/region of studies, NAFLD diagnostic methods, sex, the average age and body mass index (BMI) of NAFLD participants and assessed the risk of bias with Agency for Healthcare Research and Quality (AHRQ) methodology checklist. Risk ratio (RR) of NAFLD prevalence in former smokers was pooled using the random-effects model.Results 28 studies involving 4 465 862 participants were included. Compared with current smokers, the RR of overall NAFLD prevalence in former smokers was 1.13 (95% CI: 1.08 to 1.19, prediction interval: 0.92–1.39). This result persisted after adjustment for diagnostic methods, country/region, sex, age and BMI. Sensitivity analysis and risk of bias assessment indicated a stable conclusion.Conclusions NAFLD prevalence in former smokers was at least not lower than that in current smokers and was partially related to increased BMI after smoking cessation, indicating that smoking cessation was possibly not a protective factor against NAFLD. Although the meta-analysis based on cross-sectional studies cannot conclude the causal relationships between smoking cessation and NAFLD onset, the potential onset of NAFLD associated with smoking cessation should be highlighted.PROSPERO registration number CRD42023394944.